Health-related Quality of Life and Compensating Income Variation for 18 Health Conditions in Iceland - Hanna Björg Henrysdóttir 1984- (2016)
Viðskiptafræðideild hefur samþykkt lokaðan aðgang að þessari ritgerð í tvö ár. Using data from an Icelandic health and well-being survey, carried out in 2007, 2009 and 2012, we estimate the monetary compensation needed to maintain the same level of well-being with and without specific health conditions. Specifically, 18 health problems are evaluated using a compensating income variation (CIV) approach. This approach employs measurements of individuals’ well-being using a population sample and with no hypothetical situations involved, thus offering a solution to biases of often used methods to value non-marketed goods. Results from our CIV analyses indicate that 1,301,758 USD are needed per year to compensate for the presence of melancholy, 159,301 USD are needed to compensate for frequent headaches, 118,465 USD are needed per year to compensate for severely low vision and for severe monthly menstrual cramps 62,419 USD per year are needed. This research adds to the CIV literature by providing an interesting starting point for further research employing the CIV method to health and provides important knowledge on the monetary value of several health conditions. Furthermore, since several different health conditions were valued with the same sample and same methodology this research provides a ranking between the conditions, aiding policy makers in prioritizing scarce resources. Erfitt getur verið að meta virði heilsu, en til að hægt sé að taka þjóðhagslega skynsamar ákvarðanir og ráðstafa fé innan heilbrigðskerfisins á sem bestan hátt þarf að liggja fyrir verðmat á heilsu. Algengar aðferðir sem notaðar eru til að verðmeta heilsu eru greiðsluviljaaðferðir sem byggja á beinum athugunum eða ímynduðum aðstæðum þar sem einstaklingur á að meta þá upphæð sem hann er reiðubúinn að greiða til að sleppa við ákveðnar aðstæður. Í þessari rannsókn eru gögn úr könnun um heilsu og líðan Íslendinga frá árunum 2007, 2009 og 2012 notuð til að verðmeta átján heilsukvilla. Tölfræðilegt samband vellíðunar, tekna og heilsukvilla er ...